THE MODEL CODE OF CIVIL LITIGATION OF THE COMMONWEALTH OF INDEPENDENT STATES AS A WAY OF CIVIL PROCEDURE HARMONIZATION - Terekhov, Victor (Teisė, 2015)
The article addresses the Model Code of Civil Litigation of the Commonwealth of Independent States (CIS) as an example of harmonization (approximation) method of civil procedural norms of the Member States of this organization. Herewith the positive and negative sides of the model law are explored, both those common for all acts of such type and those that are connected directly with the project of the Code. A conclusion on the reasons of the Code’s failure is made as well as author’s own opinion on the possibility of future adoption of other model-type procedural acts within the framework of the CIS.